Cannibalistic exchanges with mountain‐ancestors: Moral economies of gold mining in northern Peru. - Bacigalupo, Ana Mariella (Journal of Latin American & Caribbean Anthropology, 2024)
Campesinos (peasants) and norteños (northerner entrepreneurs) in highland Huamachuco, la Libertad, northern Peru—reconcile their mining within Andean practices about the perceived sentience and agency of mountain‐ancestors (apus). They do so by engaging in two different types of apu cannibalism that are antithetical to each other. I analyze how the conflict between Andean campesino communities who practice small‐scale underground mining on the apu El Toro site, and, the Summa Gold open‐pit mining company (owned by former campesinos now norteño) also on apu El Toro, reshapes, on both sides, relationalities with mountain‐ancestors and capitalism. I explore miners' practical moral economies with apus, the local government, and legal authorities to secure economic and political benefits as their worlds are transformed by capitalism. I also analyze how the power inequality between campesino and norteño miners shapes these exchanges, their ability to control the limits of extractivism, and the rhetoric around mining contamination.